#z_Legacy/Maths/A-Levels/Pure/Trig-Identities
[!example]- Proof
- Consider a right triangle with an angle
$x$ .- Let the hypotenuse be of length 1.
- According to the definitions of sine and cosine, we have:
$$\sin x = \frac{\text{opposite}}{\text{hypotenuse}} = \frac{a}{1} = a$$ and$$\cos x = \frac{\text{adjacent}}{\text{hypotenuse}} = \frac{b}{1} = b,$$ - By the Pythagorean theorem, we know that in a right triangle:
$$a^2 + b^2 = 1^2$$ Substituting the values of$a$ and$b$ in terms of$\sin x$ and$\cos x$ , we get:$$\sin ^2(x) + \cos^2(x) = 1$$
[!example]- Proof
- Take
$$\sin ^2(x) + \cos^2(x) = 1$$ - Divide by
$sin^2(x)$ to get$$\frac{sin ^2(x)}{sin ^2(x)} + \frac{cos^2(x)}{sin ^2(x)} = \frac{1}{sin ^2(x)}$$ - Rearrange to get
$$1 + \left (\frac{cos(x)}{sin(x)} \right)^2 \equiv \left (\frac{1}{sin(x)} \right)^2$$ - Simplify to get
$$1 + tan^2(x) \equiv sec^2(x)$$
[!example]- Equation $$sign(a)\left(\sqrt{a^{2}+b^{2}}\right)\sin\left(x + \arctan\left(\frac{b}{a}\right)\right)$$ or $$sign(b)\left(\sqrt{a^{2}+b^{2}}\right)\cos\left(x-\arctan\left(\frac{a}{b}\right)\right)$$